Glucocorticoid metabolism and the action of 11 beta-hydroxysteroid dehydrogenase 2 in canine congestive heart failure. (April 2020) - Bode, E.F.; Markby, G.R.; Boag, A.M.; Martinez-Pereira, Y.; Corcoran, B.M.; Farquharson, C.; Sooy, K.; Homer, N.Z.M.; Jamieson, P.M.; Culshaw, G.J.
Highlights: 11 beta-hydroxysteroid dehydrogenase 2 expression was not altered in canine heart failure. 11 beta-hydroxysteroid dehydrogenase 2 activity was not altered in canine heart failure. 20α-hydroxysteroid dehydrogenase activity was elevated in canine heart failure. Total serum cortisol was not altered in canine congestive heart failure. Abstract: The enzyme 11-beta-hydroxysteroid dehydrogenase isoenzyme 2 (11BHSD2) is responsible for converting the active glucocorticoid cortisol to inactive cortisone and in the renal medulla protects the mineralocorticoid receptor (MR) from activation by cortisol. Derangements in 11BHSD2 activity can result in reduced conversion of cortisol to cortisone, activation of the MR by cortisol and, consequently, sodium and water retention. The objective of this study was to examine glucocorticoid metabolism in canine congestive heart failure (CHF), specifically to evaluate whether renal 11BHSD2 activity and expression were altered. Dogs were prospectively recruited into one of two phases; the first phase ( n  = 56) utilized gas chromatography-tandem mass spectrometry to examine steroid hormone metabolites normalised to creatinine in home-caught urine samples. Total serum cortisol was also evaluated. The second phase consisted of dogs ( n  = 18) euthanased for refractory CHF or for behavioural reasons. Tissue was collected from the renal medulla for examination by quantitative reverse transcription polymerase chain reaction, immunohistochemistry and protein immune-blotting. Heart failure did not change urinary cortisol:cortisone ratio ( P  = 0.388), or modify renal expression ( P  = 0.303), translation ( P  = 0.427) or distribution of 11BHSD2 ( P  = 0.325). However, CHF did increase excretion of 5α-tetrahydrocortisone ( P  = 0.004), α-cortol ( P  = 0.002) and α-cortolone ( P  = 0.009). Congestive heart failure modifies glucocorticoid metabolism in dogs by increasing 5α-reductase and 20α-hydroxysteroid dehydrogenase activity. Differences between groups in age, sex and underlying disease processes may have influenced these results. However, 11BHSD2 does not appear to be a potential therapeutic target in canine CHF.